1997
DOI: 10.1016/s0014-5793(97)00043-4
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin 4‐sulphate exhibits inhibitory effect during Cu2+‐mediated LDL oxidation

Abstract: Chondroitin 4-sulphate (C4S), a basic component of the extracellular matrix of the artery wall, inhibited copperinduced low density lipoprotein (LDL) oxidation by prolonging the lag time and reducing the rate of propagation. LDL oxidation was assessed by monitoring conjugated dienes and low level chemiluminescence. A possible initial key reaction in LDL oxidation, the reduction of copper(II) to copper(I) by LDL, was decreased in the presence of C4S. Moreover, C4S protected tryptophan residues of Apo-B-100 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Chondroitin 4-sulfate inhibited the cytoadherence of P. falciparum-infected erythrocytes to melanoma cells, whereas chondroitin 6-sulfate had little or no effect (38). Chondroitin 4-sulfate, but not chondroitin 6-sulfate, exhibited an inhibitory effect during Cu 2ϩ -mediated low density lipoprotein oxidation (39). Chondroitin 6-sulfate inhibited neurite growth from rat cerebellar and dorsal root ganglion neurons, whereas chondroitin 4-sulfate stimulated elongation of dorsal root ganglion neurites (40).…”
Section: Discussionmentioning
confidence: 95%
“…Chondroitin 4-sulfate inhibited the cytoadherence of P. falciparum-infected erythrocytes to melanoma cells, whereas chondroitin 6-sulfate had little or no effect (38). Chondroitin 4-sulfate, but not chondroitin 6-sulfate, exhibited an inhibitory effect during Cu 2ϩ -mediated low density lipoprotein oxidation (39). Chondroitin 6-sulfate inhibited neurite growth from rat cerebellar and dorsal root ganglion neurons, whereas chondroitin 4-sulfate stimulated elongation of dorsal root ganglion neurites (40).…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that 6-sulfated CS increases the susceptibility of lipoproteins to oxidized in vitro (Camejo et al, 1998). In contrast, 4-sulfated CS exhibits anti-atherogenic properties, since it prevents Cu 2+ induced LDL and HDL oxidation (Albertini, et al, 1997.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules may be distinguishable as a function of their degree of sulphation at the C-4 or C-6 positions of galactosamine. C4S exhibited the greatest antioxidant effect among CS (Campo et al, 2004b;Albertini et al, 1997).…”
Section: Discussionmentioning
confidence: 94%